A green and recyclable CuSO4·5H2O/ionic liquid catalytic system for the CO2-promoted hydration of propargyl alcohols: an efficient assembly of α-hydroxy ketones; Journal of Catalysis; Vol. 405 - Yuan Ye; Jia Hu; Yu Wang; Leilei Huang; Jiayun Zheng; Yufeng Zhao; Yiyun Chen; Cheng Chen; Verpoort F. V. K. Frensis Valter Kornelius (2022, 2022)
Title screen